Motivasi Belajar Terhadap Kemampuan Berpikir Kreatif Matematis Pada Siswa - Deta Virgia Septi; Mia Khusnunisa; M. Afrilianto (Journal on Education, 2019)
Creative thinking is one of the abilities to create ideas and the latest ideas so that they can achieve their goals in life. The method used in this study is a descriptive qualitative method that aims to be able to analyze the students' work on creative thinking questions. The research population of students in SMP Negeri 2 Serang Baru with sample subjects was students of class VIII 2, amount 36 students. As for the test being used is the ability of mathematical creative thought with 8 questions and non-motivation test instruments 35 questions for each student. The results of the analysis obtained were that the ability to think creatively in junior high schools in Bekasi regency based on written description tests was still relatively easy and students' learning activeness was still lacking